Ameliorating diabetes-associated atherosclerosis and diabetic nephropathy through modulation of soluble guanylate cyclase - Sharma, Arpeeta; Choi, Judy; Sim, Lachlan; Dey, Abhiroop; Mohan, Muthukumar; Kantharidis, Phillip; Dietz, Lisa; Sandner, Peter; de Haan, Judy B. (Frontiers in Cardiovascular Medicine, 2023)
Diabetes mellitus (DM) is an independent risk factor for micro- and macrovascular complications such as nephropathy and atherosclerosis respectively, which are the major causes of premature morbidity and mortality in Type 1 and Type 2 diabetic patients. Endothelial dysfunction is the critical first step of vascular disease and is characterized by reduced bioavailability of the essential endothelial vasodilator, nitric oxide (NO), coupled with an elevation in inflammation and oxidative stress. A novel pathway to bolster NO activity is to upregulate soluble guanylate cyclase (sGC), an enzyme responsible for mediating the protective actions of NO. Two classes of sGC modulators exist, activators and stimulators, with differing sensitivity to oxidative stress. In this study, we investigated the therapeutic effects of the sGC stimulator BAY 41-2272 (Bay 41) and the sGC activator BAY 60-2770 (Bay 60) on endpoints of atherosclerosis and renal disease as well as inflammation and oxidative stress in diabetic Apolipoprotein E knockout (ApoE-/-) mice. We hypothesized that under oxidative conditions known to accompany diabetes, sGC activation might be more efficacious than sGC stimulation in limiting diabetic vascular complications. We demonstrate that Bay 60 not only significantly decreased nitrotyrosine staining (P < 0.01) and F4/80 positive cells by 75% (P < 0.05), but it also significantly reduced total plaque area (P < 0.05) and improved endothelial function (P < 0.01). Our data suggest an important anti-atherogenic role for Bay 60 accompanied by reduced oxidative stress and inflammation under diabetic settings. Treatment with the stimulator Bay 41, on the other hand, had minimal effects or caused no changes with respect to cardiovascular or renal pathology. In the kidneys, treatment with Bay 60 significantly lessened urinary albuminuria, mesangial expansion and nitrotyrosine staining under diabetic conditions. In summary, our head-to-head comparator is the first preclinical study to show that a sGC activator is more efficacious than a sGC stimulator for the treatment of diabetes-associated vascular and renal complications.